Measurement of Ξ + 𝑐 production in 𝑝⁢Pb collisions at √𝑠𝑁⁢𝑁=8.16 TeV at LHCb - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Leverington, Blake; Marks, Jörg; Morgenthaler, Maurice Pierre; et al. (Physical review, 2024)
A study of prompt Ξ+𝑐 production in proton-lead collisions is performed with the LHCb experiment at a center-of-mass energy per nucleon pair of 8.16 TeV in 2016 in 𝑝⁢Pb and Pb⁢𝑝 collisions with an estimated integrated luminosity of approximately 12.5 and 17.4 nb−1, respectively. The Ξ+𝑐 production cross section, as well as the Ξ+𝑐 to Λ+𝑐 production cross-section ratio, are measured as a function of the transverse momentum and rapidity and compared to the latest theory predictions. The forward-backward asymmetry is also measured as a function of the Ξ+𝑐 transverse momentum. The results provide strong constraints on theoretical calculation and are a unique input for hadronization studies in different collision systems.